Pillar fire hydrants - specification (DSM, 2014)
This Malaysian Standard specifies the minimum requirements for the design, materials, manufacture, test methods, marking and evaluation of conformity for pillar hydrants for fire fighting purposes, with the following characteristics: a) sizes DN 100 and DN 150; b) suitable for an allowable operating pressure, PFA, of PN 16 with or without drain facility; c) having vertical or horizontal, flanged, socket or spigot inlet; and d) with two or three outlets.